Land Price Model for Sholinganallur Town in Chennai Metropolitan Area - Sampathkumar, V.; Helen Santhi, M. (Indian Journal of Marketing, 2010)
In this paper, empirical data and statistical models are employed to forecast the land price and to quantify the interaction behaviour of factors at Sholinganallur which is located on IT Corridor in Chennai. The monthly average of the factors such as National Gross Domestic Product, cost of crude oil, dollar equivalence to Indian currency, rate of inflation, gold and silver price, Mumbai and National share index, population in the study area, interest rate on home loan, unit cost of construction, guide line value and time factor from the year 1997 to 2008 are considered to develop a step-wise backward regression model to forecast the trend of land price. Out of thirteen factors, nine factors show good response in the model. An annual factor model is also developed for the year 2008 using physical parameters.